From a word to a world: the current situation in the interdisciplinary field of synthetic biology - Hu, Xiaojun; Rousseau, Ronald (PeerJ, 2015)
Using a carefully designed search query, we describe the field of synthetic biology in terms of leading countries, organizations and funding sources. Besides articles we also paid some attention to patents. The USA is the leading country in this field, followed by China. There is a clear exponential growth in the field of synthetic biology over the latest 14 years. Keywords were analyzed using the notion of year-based h-indices, core gap and relative core gap. We conclude that the term “synthetic biology” hides a large world ready to be explored by interdisciplinary research.
Keywords: Query formulation; Synthetic biology; Year-based h-indices; Keyword analysis